The Relationship Between Workers’ Health and Night Shift Work in Food Franchise Industry in Kuching, Sarawak, Malaysia - Siew, Wui Long; Florianna Lendai, Michael Mulok; Hana, Hamidi (Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS), 2018)
Shift work alters workers exposure to natural and artificial light, sleep patterns, and feeding patterns. Among other working population, shift workers are at a greater risk of developing metabolic impairments over time. Hence, this study aimed to study the relationship between workers’ health and night shift work in food franchise industry in Kuching, Sarawak. The independent variables are sleep pattern, mental health, psychological well-being, circadian rhythm, and insomnia, while the dependent variable is night shift work. Questionnaires were distributed using convenience sampling techniques and a total of 59 questionnaires were collected. Pearson Correlations test. showed that there is a significant relationship between workers’ health and night shift work. The implications on this research shows that there are more researches on the mitigation of health risk on shift workers.